Blocking autofluorescence in brain tissues affected by ischemic stroke, hemorrhagic stroke, or traumatic brain injury - Wang, Shaoshuai; Ren, Xiuhua; Wang, Junmin; Peng, Qinfeng; Niu, Xiaoyu; Song, Chunhua; Li, Changsheng; Jiang, Chao; Zang, Weidong; Zille, Marietta; Fan, Xiaochong; Chen, Xuemei; et al. (Frontiers in Immunology, 2023)
Autofluorescence is frequently observed in animal tissues, interfering with an experimental analysis and leading to inaccurate results. Sudan black B (SBB) is a staining dye widely used in histological studies to eliminate autofluorescence. In this study, our objective was to characterize brain tissue autofluorescence present in three models of acute brain injury, including the collagenase-induced intracerebral hemorrhage (ICH) model, the traumatic brain injury model (TBI), and the middle cerebral artery occlusion model, and to establish a simple method to effectively block autofluorescence. We examined autofluorescence in brain sections affected by ICH and TBI using fluorescence microscopy. We optimized a protocol to block autofluorescence with SBB pretreatment and evaluated the reduction in fluorescence intensity. Compared to untreated, pretreatment with SBB reduced brain tissue autofluorescence in the ICH model to 26.32% (FITC), 23.95% (Tx Red), and 28.12% (DAPI), respectively. In the TBI model, the ratio of pretreatment to untreated decreased to 43.15% (FITC), 55.72% (Tx Red), and 53.64% (DAPI), respectively. Furthermore, we tested the applicability of the protocol using immunofluorescence staining or CY5.5 labeling in the three models. SBB treatment is highly effective and can be applied to immunofluorescence and fluorescence label imaging techniques. SBB pretreatment effectively reduced background fluorescence but did not significantly reduce the specific fluorescence signal and greatly improved the signal-to-noise ratio of fluorescence imaging. In conclusion, the optimized SBB pretreatment protocol blocks brain section autofluorescence of the three acute brain injury models.